Revitalization of ancient Indonesian characters and the maintenance efforts in past 10 years - Arif Hidayat (Mitra Palupi, 2021)
Background: This mixing of cultures will also create a cultural reproduction that has the potential for diversity. This culturally diverse country, of course, has a lot of characters from various regions and cultures. Purpose: this research is expected to be a means to reopen the repertoire of the diversity of characters in Indonesia that has begun to be forgotten. In this study, the author will reveal a number of efforts to maintain the Indonesian script. Design and methods: the research design were using the library research method. Sources of data used in this study are in the form of documents, books, journals, digital applications obtained through the internet network. Results: The heritage of Indonesian characters is very diverse with the plurality of tribes in Indonesia. With the support of the development of information technology, the revitalization of Indonesian script culture is very possible to be popularized again.